Nomogram for predicted probability of cervical cancer and its precursor lesions using miRNA in cervical mucus, HPV genotype and age - Kotani, Kiriko; Iwata, Aya; Kukimoto, Iwao; Nishio, Eiji; Mitani, Takeji; Tsukamoto, Tetsuya; Ichikawa, Ryoko; Nomura, Hiroyuki; Fujii, Takuma (Scientific reports, 2022)
Cervical cancer is the fourth most common cancer in women worldwide. Although cytology or HPV testing is available for screening, these techniques have their drawbacks and optimal screening methods are still being developed. Here, we sought to determine whether aberrant expression of miRNAs in cervical mucus could be an ancillary test for cervical neoplasms. The presence of miRNAs in 583 and 126 patients (validation and external cohorts) was determined by real-time RT-PCR. Performance of a combination with five miRNAs (miR-126-3p, -451a -144-3p, -20b-5p and -155-5p) was estimated by ROC curve analysis. Predicted probability (PP) was estimated by nomograms comprising -ΔCt values of the miRNAs, HPV genotype and age. A combination of five miRNAs showed a maximum AUC of 0.956 (95% CI: 0.933–0.980) for discriminating cancer. Low PP scores were associated with good prognosis over the 2-year observation period ( p < 0.05). Accuracy for identifying cancer and cervical intraepithelial neoplasia (CIN) 3 + by nomogram was 0.983 and 0.966, respectively. PP was constant with different storage conditions of materials. We conclude that nomograms using miRNAs in mucus, HPV genotype and age could be useful as ancillary screening tests for cervical neoplasia.